Templo religioso, natureza e os avanços tecnológicos: os saberes do candomblé na contemporaneidade - Iyagunã, Dalzira Maria Aparecida (2013)
This research intend to develop a qualitative study to investigate the relationship between technology and traditional knowledge in traditional Candomblé in three terraces of different nations. The following nations are: Ketu, Jêje and Bantu. The yard Ketu is located in the city of Salvador, the yard Jêje recôncavo located in Bahia, in Cachoeira and the third yard, Bantu, located in the city of St. Joseph of the Pines, metropolitan region of Curitiba-PR, this being one rural yard. The purpose of this study these three terraces is observed the relationship between the internet and Candomblé considering analyze how religion articulates this relation to nature and to the values and ancestral knowledge forward to technological advances. The methodology consisted in analyzing interviews with priestesses and priests and religious representatives of the three nations surveyed. Another focus of this work was to analyze the impacts of urbanization and loss of territoriality, and the importance of preserving the language and orality in the yards of Candomblé while the ancestry and hierarchy in the traditions of African religions in Africa and in the diaspora. The analysis has been constantly linked with a discussion of the changes in Brazilian law regarding the rights of religions of African, considering that these religions were historically discriminated associated with primitivism and barbarism. The importance of this work is to bring to the fore a permanent and necessary discussion about religious intolerance and "secular state".